Muhammadiyah as a Progressive Islamic Movement: Tajdid, Modernity, and Social Transformation in Indonesia - Nur Faidah; Miftahul Jannah Ilyas; M. Amin (Masterpiece, 2026)
This study examines Muhammadiyah as a manifestation of Progressive Islam (Islam Berkemajuan), emphasizing its role as a reformist Islamic movement in responding to the challenges of modernity, globalization, and socio-cultural change in Indonesia. Founded in 1912 by K.H. Ahmad Dahlan, Muhammadiyah has consistently promoted tajdid (renewal) as both purification of Islamic teachings based on the Qur’an and Sunnah and constructive development through rational, contextual, and future-oriented interpretations of Islam. Using a qualitative descriptive and literature-based approach, this paper analyzes the historical evolution, ideological foundations, and practical expressions of Progressive Islam within Muhammadiyah. The findings indicate that Muhammadiyah’s commitment to education, social services, healthcare, and economic empowerment demonstrates a balanced integration of religious values and modern knowledge. The movement’s emphasis on rationality, moderation, and ethical social engagement has enabled Muhammadiyah to function as an agent of social transformation and national development. Furthermore, the concept of Progressive Islam reflects Muhammadiyah’s adaptive capacity to maintain Islamic authenticity while engaging constructively with contemporary issues, including technological advancement and global interaction. This study concludes that Muhammadiyah represents a distinctive model of Progressive Islam that contributes significantly to the development of a just, prosperous, and dignified society, reinforcing its relevance as a modern Islamic movement in Indonesia and beyond.